The Relationship between Skeletal Muscle Strength and Cardiac Senescence Performance in the Elderly at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Muhammad Haryadi Ade Kurnadi; Nur Riviati; Taufik Indrajaya; Mgs. Irsan Saleh (HM Publisher, 2023)
Background: The aging process is physiological, but the onset, rate, and extent of the progression of aging at the cell, tissue, organ, and system level are very heterogeneous because they are influenced by genetic and environmental factors. The aging process is known to involve the entire body, including musculoskeletal and cardiovascular components. Several theories explain this association, including reduced muscle mass associated with chronic heart failure, decreased serum myostatin, and cross-talk between skeletal and cardiac muscle mediated by inflammatory cytokines. This study aimed to determine the relationship between skeletal muscle strength and cardiac performance in elderly patients at Dr. Mohammad Hoesin General Hospital, Palembang. Methods: This research is an analytical observational study with a cross-sectional design. The total sample size was 65 individuals who met the inclusion and exclusion criteria. Data analysis was carried out using the SPSS 25 for Windows program. Results: Handgrip strength has a significant relationship with diastolic dysfunction on a numerical scale (p=0.009). Low handgrip strength has a 3 times greater risk of experiencing diastolic dysfunction than patients with Normal Handgrip Strength. Conclusion: Skeletal muscle strength has a relationship with cardiac senescence performance in elderly patients at Dr. Mohammad Hoesin General Hospital, Palembang.